Principal Leadership Strategies for Enhancing Teacher Performance in Islamic Schools - Emi Dwi Ani; Abu Hasan Agus R; Suhermanto (Journal of Educational Management Research, 2025)
This study aims to describe and analyze the leadership practices of the madrasah principal in enhancing teacher performance. The background of this research is related to the critical role of the principal as a strategic leader in developing the quality of human resources, particularly teachers, who are the primary agents in the learning process. The generally low teacher performance in several educational institutions highlights the need for a transformative and supportive leadership approach. This research employs a descriptive qualitative method, utilizing data collection techniques that include in-depth interviews, participatory observation, and document analysis. The research subjects include the principal, teachers, students, and parents, selected purposively. The findings show that the principal applies a transformational leadership model through academic supervision, continuous monitoring, and the reinforcement of discipline and work ethic. Supervision is conducted in a humanistic and dialogical manner, directly contributing to the improvement of teachers' pedagogical competence. Monitoring serves as a development tool and a systematic performance mapping instrument. Additionally, the principal's exemplary conduct promotes discipline and collective responsibility. The improvement in teacher performance has a positive impact on the quality of learning and stakeholder satisfaction, including that of students and parents.